Chip-shaped electrode and method for manufacturing the electrode

JP7637525B2Active Publication Date: 2025-02-28SUMITOMO CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021021139
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-12
Publication Date
2025-02-28
Estimated Expiration
2041-02-12

AI Technical Summary

Benefits of technology

【0006】 本開示によれば、加工が容易であり、加工歩留りが高く、信頼性の高い、ダイヤモンド部を有する電極を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637525000002
    Figure 0007637525000002
  • Figure 0007637525000003
    Figure 0007637525000003
  • Figure 0007637525000004
    Figure 0007637525000004
Patent Text Reader

Abstract

To provide an electrode including a diamond part that is easily processed, high in processing yield and has high reliability.SOLUTION: The electrode includes a support formed of a material other than diamond, and a diamond part supported on a supporting surface which is one of surfaces included in the support. The diamond part is composed of a plurality of granular diamond crystals, and part of the supporting surface is exposed.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to electrodes and methods for making electrodes. [Background technology]

[0002] In recent years, it has been proposed to use an electrode having a diamond film as the working electrode of an electrochemical sensor (see, for example, Patent Documents 1 and 2). Diamond, which has electrical conductivity, has a wide potential window and a small background current, allowing electrochemical detection of various substances such as uric acid with high sensitivity. For this reason, diamond, which has electrical conductivity, has attracted attention as a material for forming a working electrode. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-292717 A [Patent Document 2] JP 2013-208259 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, since diamond is a material with high hardness, there are problems in that electrodes having diamond films are difficult to process and have low processing yields, etc. The present disclosure aims to provide an electrode having a diamond portion that is easy to process, has a high processing yield, and is also highly reliable. [Means for solving the problem]

[0005] According to one aspect of the present disclosure, A support formed of a material other than diamond; a diamond portion supported on a support surface which is at least one of the surfaces of the support; The diamond portion is composed of a plurality of granular diamond crystals, An electrode and method for making the same are provided, wherein a portion of the support surface is exposed. Effect of the Invention

[0006] According to the present disclosure, it is possible to provide an electrode having a diamond portion that is easy to process, has a high processing yield, and is highly reliable. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a diagram showing a longitudinal section of an electrode according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic plan view of an electrode according to one embodiment of the present disclosure, viewed from above (the diamond portion side). [Diagram 3] FIG. 1 is a schematic diagram of a vapor phase growth apparatus used to grow diamond crystals. [Figure 4] 4(a) is a diagram showing the cross-sectional structure of a laminate (laminated wafer) of a diamond portion and a substrate, (b) is a cross-sectional view showing the formation of a groove on the back surface of the laminate shown in FIG. 4(a), and (c) is a schematic diagram showing the state in which the support is broken along the groove to obtain a working electrode. [Diagram 5] FIG. 13 is a diagram showing the evaluation results of Sample 1. [Figure 6] FIG. 13 is a diagram showing the evaluation results of Sample 2. [Figure 7] FIG. 13 is a diagram showing the evaluation results of Sample 3. [Figure 8] FIG. 13 is a diagram showing the evaluation results of Sample 4. [Figure 9] FIG. 13 is a diagram showing the evaluation results of Sample 5. [Figure 10] FIG. 13 is a diagram showing the evaluation results of Sample 6. [Figure 11] FIG. 13 is a diagram showing the evaluation results of Sample 7. [Figure 12] FIG. 13 is a diagram showing the evaluation results of sample 8. [Figure 13]FIG. 1 is a diagram showing an example of a perspective view of an electrochemical sensor using an electrode according to an embodiment of the present disclosure as a working electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] <One aspect of the present disclosure> Hereinafter, one embodiment of the present disclosure will be described with reference to FIGS.

[0009] The electrode according to the present embodiment can be suitably used as a working electrode in electrochemical measurements. For example, the electrode according to the present embodiment can be suitably used as a working electrode of an electrochemical sensor that measures the concentration of a specific component contained in a test solution (electrolyte solution) by a two-electrode method or a three-electrode method.

[0010] As shown in FIG. 1, the electrode 10 is configured as a laminate having a diamond portion 11 and a support 12 that supports the diamond portion 11. The electrode 10 having the diamond portion 11 is sometimes called a diamond electrode. When the electrode 10 is used as a working electrode of an electrochemical sensor, the diamond portion 11 causes an electrochemical reaction of a specific component (predetermined reactive species) in a test liquid on its surface. For example, in a sensor having an electrode group including the electrode 10 and a counter electrode, when urine is supplied to the sensor as a test liquid, and a predetermined voltage is applied to the electrode group with urine attached thereto, the diamond portion 11 causes an oxidation-reduction reaction of uric acid on its surface.

[0011] The electrode 10 has a rectangular outer shape, for example a square outer shape, in a plan view. That is, the electrode 10 is formed in a chip shape (see FIG. 2). The planar area of ​​the electrode 10 is, for example, 25 mm 2 From the viewpoint of producing a chip-shaped electrode 10, the plane area of ​​the electrode 10 can be, for example, 1 mm 2 It is preferable that the surface area is 1 mm or more. 2 The above-mentioned electrode 10 can be manufactured easily and stably with high accuracy by a method using fracture described later. 2By satisfying the above, it is also possible to suppress deterioration in the handling properties of the electrode 10 and deterioration in the mounting stability.

[0012] The diamond portion 11 is supported (provided) on at least one of the surfaces of the support 12. Hereinafter, the surface of the support 12 that supports the diamond portion 11 is also referred to as a support surface 12s.

[0013] As shown in FIG. 2, the diamond portion 11 is composed of a plurality of granular crystals made of diamond, i.e., a plurality of granular diamond crystals. The diamond portion 11 may be composed of a plurality of granular crystals made of diamond-like carbon (DLC), i.e., a plurality of granular DLC crystals. Hereinafter, the granular diamond crystals and the granular DLC crystals are collectively referred to as "granular crystals 11a". The diamond portion 11 can be grown (synthesized) by using, for example, a hot filament CVD method using a tungsten filament, a chemical vapor deposition (CVD) method such as a plasma CVD method, or a physical vapor deposition (PVD) method such as an ion beam method or an ionization deposition method. The diamond portion 11 is preferably p-type. The diamond portion 11 may be formed by doping an element (dopant) such as boron (B) at a concentration of, for example, 1×10 19 cm -3 More than 1×10 22 cm -3 Concentration of 1×10 or less, preferably 1×10 20 cm -3 5×10 or more 21 cm -3 By including the following concentration, diamond portion 11 can be made p-type. That is, diamond portion 11 is preferably composed of granular crystals 11a including B element in the above-mentioned predetermined range. The B concentration in diamond portion 11 can be measured by, for example, secondary ion mass spectrometry (SIMS).

[0014] Since the diamond portion 11 is not a continuous film (hereinafter also referred to as a diamond film) made of diamond (or DLC) but is composed of a plurality of granular crystals 11a, the diamond portion 11 has gaps and spaces between the granular crystals 11a (hereinafter collectively referred to as simply "gaps").

[0015] By having gaps in the very hard (high hardness) diamond portion 11, the diamond portion 11 can be separated at the gaps between the granular crystals 11a, which makes it easy to mold the electrode 10. For example, by simply breaking (fracturing) the support 12 of the laminate (i.e., the laminated wafer 20 described below) of the diamond portion 11 and the support 12 before molding into the electrode 10, it is possible to obtain the chip-shaped electrode 10 with good accuracy and stability. In this way, by having gaps in the diamond portion 11, it is possible to improve the processing yield and processing accuracy of the electrode 10. In addition, it is possible to reduce the size of the electrode 10, which makes it possible to improve the productivity of the electrode 10.

[0016] In addition, when there is a difference between the thermal expansion coefficient of diamond (or DLC) and the thermal expansion coefficient of the support 12, tensile stress or compressive stress may be applied in the in-plane direction of the support 12 due to the difference in the amount of thermal contraction between the diamond part 11 and the support 12. Even if there is a difference between the thermal expansion coefficient of diamond and the thermal expansion coefficient of the support 12, the diamond part 11 has gaps, so that the stress caused by the difference in the thermal expansion coefficients can be released and relaxed through the above-mentioned gaps. As a result, it is possible to prevent the diamond part 11 (granular crystals 11a) from peeling off from the support 12 (support surface 12s). This makes it possible to prevent a decrease in the diamond part 11 that contributes to sensing, and to prevent a decrease in the sensitivity of the electrode 10. As a result, it is also possible to improve the reliability of the electrode 10 and the reliability of a sensor having the electrode 10.

[0017] Furthermore, by alleviating the stress caused by the difference in thermal expansion coefficients, the laminate (laminated wafer 20 described below) of diamond portion 11 and support 12 before being formed into electrode 10 is less likely to warp. Also, the residual stress in diamond portion 11 can be reduced, and preferably eliminated. As a result, electrode 10 can be obtained easily from laminated wafer 20 with high accuracy and stability. In other words, the processing accuracy, processing yield, and productivity of electrode 10 can be further improved.

[0018] The diamond portion 11 is provided so as not to cover the entire surface of the support surface 12s, but to expose a part of the support surface 12s. For example, the ratio of the projected area of ​​the granular crystals 11a onto the support surface 12s to the planar area of ​​the support surface 12s is 15% or more and 90% or less, preferably 30% or more and 75% or less. In this specification, the ratio of the projected area of ​​the granular crystals 11a onto the support surface 12s to the planar area of ​​the support surface 12s (= (projected area of ​​the granular crystals 11a / planar area of ​​the support surface 12s) × 100) is also referred to as the "coverage rate". That is, the coverage rate of the support surface 12s by the diamond portion 11 is, for example, 15% or more and 90% or less, preferably 30% or more and 75% or less.

[0019] By setting the coverage to 15% or more, the surface area of ​​the diamond portion 11 can be set to a predetermined value or more, which allows the electrode 10 to be suitably used as a working electrode of an electrochemical sensor.

[0020] Moreover, by having a coverage rate of 15% or more and 90% or less, the total surface area of ​​the diamond portion 11 that can contribute to sensing (hereinafter also referred to as the surface area of ​​the diamond portion 11) can be made larger than the plane area of ​​the support surface 12s. Also, the surface area of ​​the diamond portion 11 can be made larger than when the coverage rate is over 90% or when the diamond portion 11 is made of a diamond film. This makes it possible to increase the sensitivity of the electrode 10, and to increase the accuracy of electrochemical measurement using a sensor with the electrode 10 as the working electrode. For example, when the concentration of uric acid in a test liquid is measured by cyclic voltammetry using a sensor having the electrode 10, the oxidation current peak (value) observed in the obtained cyclic voltammogram is higher than when the coverage rate is over 90% or when the diamond portion 11 is made of a diamond film. As a result, it becomes possible to measure the concentration of uric acid in the test liquid more accurately.

[0021] Moreover, since the coverage is 90% or less, it is possible to reliably obtain the diamond portion 11 having gaps. This makes it possible to reliably improve the processing yield and processing accuracy of the electrode 10. In addition, the effect of relieving the stress caused by the above-mentioned difference in thermal expansion coefficient (hereinafter also referred to as the "stress relaxation effect") is easily obtained, making it possible to reliably prevent the granular crystals 11a from peeling off.

[0022] Moreover, since the coverage is 75% or less, it is possible to obtain the diamond portion 11 having sufficient gaps. This makes it possible to further improve the processing yield and processing accuracy of the electrode 10. In addition, the above-mentioned stress relaxation effect can be reliably obtained, and it is possible to more reliably prevent the granular crystals 11a from peeling off. As a result, it is possible to further improve the accuracy of the electrochemical measurement.

[0023] Furthermore, by having the coverage rate of 30% or more and 75% or less, it is possible to increase the surface area of ​​the diamond portion 11. As a result, it is possible to further increase the sensitivity of the electrode 10, and to further increase the accuracy of the electrochemical measurement.

[0024] The average grain size of the granular crystals 11a can be, for example, 60 nm or more and 150 nm or less, preferably 75 nm or more and 125 nm or less. The average grain size here is the average grain size in the cross section of the diamond part 11 in the planar direction of the support surface 12s of the support 12. The average grain size of the granular crystals 11a can be obtained by image analysis of the field of view of an image taken by a scanning electron microscope (e.g., SEM image) or an image taken by a transmission electron microscope (e.g., TEM image). Specifically, first, an SEM image or a TEM image is obtained, and the grain size distribution of the granular crystals 11a is measured based on the SEM image or the TEM image. Next, individual grains are extracted using image analysis software (e.g., ScionImage, manufactured by Scion Corporation), and the extracted grains are binarized to calculate the area (S) of each grain. Then, the grain size (D) of each grain is calculated as the diameter (D=2√(S / π)) of a circle having the same area. Next, the particle size distribution obtained above is processed by data analysis software (for example, Origin manufactured by OriginLab, Mathchad manufactured by Parametric Technology, etc.) to calculate the average particle size.

[0025] By setting the average particle size to, for example, 60 nm or more, it is possible to avoid the manifestation of adverse effects caused by the grain boundaries between the granular crystals 11a. For example, even if there is a region (localized region, dense region) on the support surface 12s where the granular crystals 11a are densely present, it is possible to avoid an increase in dark current during electrochemical measurement, and it is possible to avoid an increase in the noise level in a sensor having the electrode 10. Note that the dark current here is a current that flows between the working electrode and the counter electrode when a current value generated by an oxidation-reduction reaction is not measured in a state where a predetermined voltage is applied to the electrode group (working electrode, counter electrode, reference electrode) of the sensor. Also, for example, even if there is a region (non-dense region) on the support surface 12s where the granular crystals 11a are sparsely present, it is possible to avoid a decrease in the output current (detection output signal) in the sensor having the electrode 10, and it is possible to avoid a decrease in the S / N ratio. In this way, by avoiding the manifestation of adverse effects caused by the grain boundaries between the granular crystals 11a, it is possible to further improve the reliability of the electrode 10 and the accuracy of the electrochemical measurement.

[0026] Moreover, by setting the average particle size to, for example, 60 nm or more, the coverage rate can be easily set to 15% or more.

[0027] By setting the average grain size to 75 nm or more, it is possible to reliably prevent adverse effects caused by grain boundaries between the granular crystals 11a from becoming apparent, and it is also possible to easily set the coverage rate to 30% or more.

[0028] By setting the average grain size to 150 nm or less, it is possible to reliably obtain diamond portions 11 having gaps. Also, the coverage rate can be easily set to 90% or less.

[0029] By setting the average grain size to 125 nm or less, it is possible to reliably obtain diamond portions 11 having sufficient gaps. Also, the coverage rate can be easily set to 75% or less.

[0030] The granular crystals 11a are present randomly on the support surface 12s. "The granular crystals 11a are present randomly" means that the multiple granular crystals 11a are present on the support surface 12s without any regularity and without being extremely localized (distributed unevenly). "The multiple granular crystals 11a are present without any regularity" includes a case where one granular crystal 11a exists independently, a case where multiple granular crystals 11a exist in contact (connected), and both of these cases. In this way, it is preferable that there is no region on the support surface 12s where the granular crystals 11a are extremely densely present or extremely sparsely present. This makes it possible to avoid variations in sensitivity within one electrode 10, that is, to make the sensitivity of the electrode 10 uniform within the surface. As a result, for example, even if a small amount of test liquid is supplied to a sensor having the electrode 10 during electrochemical measurement, accurate electrochemical measurement can be performed.

[0031] The support 12 is formed using a material (heterogeneous material) other than diamond. The support 12 can be made of a conductive material. For example, the support 12 can be a support made of simple Si or a silicon compound, that is, a conductive support containing silicon (Si). Specifically, the support 12 can be made of a silicon substrate (Si substrate). As the Si substrate, any of a single crystal Si substrate, a polycrystalline Si substrate, and a silicon carbide substrate (SiC substrate) can be used.

[0032] The support 12 is preferably p-type like the diamond portion 11, and preferably contains an element such as boron (B) at a predetermined concentration. 18 cm -3 More than 1.5 x 10 20 cm -3 Concentration of 5×10 or less 18 cm -3 More than 1.2 x 10 20 cm -3 It can be contained at the following concentration: When the B concentration in the support 12 is within the above range, the resistivity of the support 12 can be reduced, while preventing a decrease in the production yield and deterioration in performance of the support 12.

[0033] The thickness of the support 12 can be, for example, 350 μm or more. This makes it possible to use a commercially available Si substrate, such as a single crystal Si substrate or a polycrystalline Si substrate, having a diameter of 6 inches or 8 inches as the support 12 without adjusting the thickness by back-rapping. As a result, it becomes possible to increase the productivity of the electrode 10 and reduce the manufacturing cost. There is no particular limit to the upper limit of the thickness of the support 12, but the thickness of a single crystal Si substrate having a diameter of 12 inches that is currently generally available on the market is about 775 μm. Therefore, the upper limit of the thickness of the support 12 in the current technology can be, for example, about 775 μm.

[0034] As described above, the diamond portion 11 is provided so as to expose a part of the support surface 12s. For this reason, it is preferable that the support surface 12s is configured so as not to cause an oxidation-reduction reaction of uric acid on the region of the support surface 12s that is not in contact with the granular crystals 11a (hereinafter also referred to as the "exposed region of the support surface 12s") when a predetermined voltage is applied. For example, it is preferable that a process (inactivation process) is performed on the exposed region of the support surface 12s so as to suppress the occurrence of an oxidation-reduction reaction of uric acid on the exposed region of the support surface 12s when a predetermined voltage is applied, that is, the exposed region of the support surface 12s is inactivated.

[0035] The inventors of the present application have confirmed that even if the entire surface of the support surface 12s is not covered by the diamond portion 11, if the exposed area of ​​the support surface 12s is inactivated, the oxidation-reduction reaction of uric acid can be avoided on the exposed area of ​​the support surface 12s in the voltage range applied to the sensor having the electrode 10 when measuring the uric acid concentration. The voltage range applied when measuring the uric acid concentration is, for example, a voltage range including a range of more than 0V and 1V or less, preferably a voltage range including a range of 0.4V or more and 0.9V or less.

[0036] The exposed region of the support surface 12s can be inactivated by, for example, oxidizing or nitriding the exposed region of the support surface 12s. By oxidizing or nitriding the exposed region of the support surface 12s, at least the surface layer of the support 12 containing Si is oxidized or nitridized, and an insulating coating (insulating film) 14 is formed on the exposed region of the support surface 12s. Note that the insulating film 14 in this case is made of silicon oxide (SiO x ) or a film containing silicon nitride (SiN). In this manner, the passivation of the exposed region of the support surface 12s is achieved by forming the insulating film 14 on the exposed region. It is sufficient that the passivation of the exposed region of the support surface 12s is achieved only on at least the surface layer of the exposed region of the support surface 12s.

[0037] The insulating film 14 covers the entire exposed area of ​​the support surface 12s without exposing the exposed area of ​​the support surface 12s. This makes it possible to reliably prevent an oxidation-reduction reaction of uric acid from occurring in the exposed area of ​​the support surface 12s during electrochemical measurement, even if the test liquid comes into contact with the exposed area of ​​the support surface 12s.

[0038] The thickness of the insulating film 14 (e.g., the thickness of the oxidized or nitrided surface layer of the support 12) can be, for example, 1 nm or more, preferably 2 nm or more. If the insulating film 14 is 1 nm or more thick, it can cover the entire exposed area of ​​the support surface 12s. If the insulating film 14 is 2 nm or more thick, it can reliably cover the entire exposed area of ​​the support surface 12s. If the insulating film 14 is extremely thick, the conductive area of ​​the support 12 will be reduced. For this reason, it is preferable that the insulating film 14 has a thickness that can cover the entire exposed area of ​​the support surface 12s, and is as thin as possible.

[0039] In this manner, by inactivating the exposed area of ​​the support surface 12s, the electrode 10 is configured such that, when a predetermined voltage is applied, an oxidation-reduction reaction of uric acid occurs on the surface of the diamond portion 11, but an oxidation-reduction reaction of uric acid does not occur on the exposed area of ​​the support surface 12s.

[0040] (3) Electrode manufacturing method The method for producing the electrode 10 of this embodiment will be described mainly with reference to FIGS.

[0041] In the method for producing the electrode 10 of this embodiment, A step (step A) of performing a predetermined seeding treatment or scratching treatment on the surface of the support 12 that will become the support surface 12s; a step (step B) of providing a diamond portion 11 by growing a plurality of granular crystals 11a on a support surface 12s of the support 12 so that a part of the support surface 12s is exposed; A step (Step C) of passivating the exposed areas of the support surface 12s is performed.

[0042] (Step A) As the support 12, a conductive substrate, for example, a Si substrate having a circular outer shape in a plan view, is prepared. Then, a seeding process or a scratching process is performed on the surface that becomes the support surface 12s out of the two main surfaces of the support 12. The seeding process refers to a process in which diamond particles (seeds) are attached to the support surface 12s by applying a solution (dispersion liquid) in which diamond particles (preferably diamond nanoparticles) of about several nm to several tens of μm are dispersed to the support surface 12s, or by immersing the support 12 in the dispersion liquid. The scratching process refers to a process in which scratches are made on the support surface 12s using diamond abrasive grains (diamond powder) of about several μm.

[0043] The granular crystals 11a grown in step B described below grow from diamond particles attached to the support surface 12s or scratches on the support surface 12s as nuclei. Therefore, by controlling (adjusting) the seeding process or scratching process, it becomes possible to grow a plurality of granular crystals 11a randomly on the support surface 12s in step B described below.

[0044] (Step B) After step A is completed, step B is performed. Specifically, diamond crystals are grown on the support surface 12s of the support 12 by a hot filament CVD method using a tungsten filament, for example, to provide the diamond portion 11.

[0045] Diamond crystal growth can be performed, for example, using a hot filament CVD apparatus 300 as shown in Fig. 3. The hot filament CVD apparatus 300 is made of a heat-resistant material such as quartz and includes an airtight container 303 having a growth chamber 301 formed therein. A susceptor 308 for holding a support 12 is provided within the growth chamber 301. A gas supply pipe 332a for supplying nitrogen (N2) gas into the growth chamber 301, a gas supply pipe 332b for supplying hydrogen (H2) gas, a gas supply pipe 332c for supplying methane (CH4) gas or ethane (C2H6) gas as a carbon (C)-containing gas, and a gas supply pipe 332d for supplying trimethylboron (B(CH3)3, abbreviated as TMB) gas, trimethylborate (B(OCH3)3) gas, triethylborate (B(C2H5O)3) gas, or diborane (B2H6) gas as a boron (B)-containing gas are connected to the side wall of the airtight container 303. Flow rate controllers 341a to 341d and valves 343a to 343d are provided in the gas supply pipes 332a to 332d in this order from the upstream side of the gas flow. Nozzles 349a to 349d are connected to the downstream ends of the gas supply pipes 332a to 332d, respectively, for supplying the gases supplied from the gas supply pipes 332a to 332d into the growth chamber 301. An exhaust pipe 330 for exhausting the inside of the growth chamber 301 is provided on the other side wall of the airtight container 303. A pump 331 is provided in the exhaust pipe 330. A temperature sensor 309 for measuring the temperature inside the growth chamber 301 is provided in the airtight container 303. A tungsten filament 310 and a pair of electrodes (e.g., molybdenum (Mo) electrodes) 311a, 311b for heating the tungsten filament 310 are also provided in the airtight container 303. Each member of the thermal filament CVD apparatus 300 is connected to a controller 380 configured as a computer, and the controller 380 is configured to control a processing procedure and processing conditions described later by a program executed on the controller 380.

[0046] The growth of diamond crystals can be carried out, for example, by the following procedure using the above-mentioned hot filament CVD apparatus. First, the support 12 is loaded (carried) into the airtight container 303 and held on the susceptor 308. Then, while evacuating the growth chamber 301, H2 gas is supplied into the growth chamber 301. In addition, a current is passed between the electrodes 311a and 311b to start heating the tungsten filament 310. By heating the tungsten filament 310, the support 12 held on the susceptor 308 is also heated. When the tungsten filament 310 reaches a desired temperature, the inside of the growth chamber 301 reaches a desired pressure, and the atmosphere in the growth chamber 301 becomes a desired atmosphere, a C-containing gas (e.g., CH4 gas) and a B-containing gas (e.g., TMB gas) are supplied into the growth chamber 301. CH4 gas and TMB gas supplied into the growth chamber 301 are decomposed (thermally decomposed) as they pass through the tungsten filament 310 heated to a high temperature, generating methyl radicals (CH3 * ) and other active species are generated. These active species and other species are supplied onto the support 12, and diamond crystals grow thereon.

[0047] The conditions for growing diamond crystals are exemplified as follows: Substrate temperature: 600°C or higher and 1000°C or lower, preferably 650°C or higher and 800°C or lower Filament temperature: 1800°C or higher and 2500°C or lower, preferably 2000°C or higher and 2200°C or lower Pressure inside the growth chamber: 5 Torr or more and 50 Torr or less, preferably 10 Torr or more and 35 Torr or less Ratio of partial pressure of TMB gas to CH4 gas (TMB / CH4): 0.003% or more and 0.8% or less Ratio of CH4 gas to H2 gas (CH4 / H2): 2% to 5% Growth time: 30 minutes or more and 120 minutes or less, preferably 60 minutes or more and 100 minutes or less

[0048] As a result, a laminate (laminate wafer 20) of the support 12 and the diamond portion 11 is produced as shown in the schematic cross-sectional view of FIG. 4(a).

[0049] By growing diamond crystals under the above conditions, it is possible to form the diamond portion 11 with a plurality of granular crystals 11a. In addition, the B concentration in the diamond portion 11 can be set to, for example, 1×10 19 cm -3 More than 1×10 22 cm -3 It can be as follows:

[0050] In particular, by setting the time for growing the granular crystals 11a (growth time) to 30 minutes or more and 120 minutes or less, the diamond portion 11 can be provided so that a portion of the support surface 12s is exposed (so as not to cover the entire surface of the support surface 12s).

[0051] Furthermore, by setting the growth time to 30 minutes or more and 120 minutes or less, it becomes easy to set the coverage of the support surface 12s by the diamond portion 11 to, for example, 15% or more and 90% or less, and the average grain size of the granular crystals 11a to, for example, 60 nm or more and 150 nm or less. Furthermore, by setting the growth time to 60 minutes or more and 100 minutes or less, it becomes easy to set the coverage to 30% or more and 75% or less, and the average grain size of the granular crystals 11a to, for example, 75 nm or more and 125 nm or less.

[0052] As described above, the support surface 12s is subjected to a predetermined seeding or scratching treatment in step A. Therefore, by growing diamond crystals under the above-mentioned conditions, the granular crystals 11a grow randomly on the support surface 12s.

[0053] (Step C) After step B is completed, step C is performed. In this step, the region of the support surface 12s that is not in contact with the granular crystals 11a (the exposed region of the support surface 12s) is inactivated. Specifically, the stacked wafers 20 in which a part of the support surface 12s is exposed are annealed in an oxygen-containing atmosphere (O-containing atmosphere) or a nitrogen-containing atmosphere (N-containing atmosphere).

[0054] The annealing conditions are exemplified as follows: Annealing atmosphere: O2 gas, air, or N2 gas Annealing temperature: 60°C or higher and 200°C or lower, preferably 70°C or higher and 140°C or lower Annealing time: 5 minutes or more and 180 minutes or less, preferably 60 minutes or more and 120 minutes or less

[0055] By performing annealing under the above-mentioned conditions, a thermal oxide film (SiO x A silicon nitride film (SiN film) or a silicon nitride film (SiN film) can be formed, and at least the surface layer of the exposed area of ​​the support surface 12s can be passivated.

[0056] In this step, instead of the above-mentioned annealing, the stacked wafers 20 may be irradiated with ultraviolet light in an O-containing atmosphere using, for example, a mercury lamp.

[0057] The conditions for irradiation with ultraviolet light are exemplified as follows. Irradiation atmosphere: O2 gas or air Irradiation temperature: room temperature (25-28°C, e.g. 27°C) Irradiation time: 5 minutes or more and 30 minutes or less, preferably 10 minutes or more and 20 minutes or less

[0058] Irradiation with ultraviolet light under the above-mentioned conditions can also oxidize the exposed area of ​​support surface 12s, forming an ozone oxide film as insulating film 14 over the entire exposed area of ​​support surface 12s, and inactivating at least the surface portion of the exposed area of ​​support surface 12s.

[0059] In this step, instead of the above-mentioned annealing or ultraviolet light irradiation, the stacked wafers 20 may be left in a clean atmosphere, such as in a clean bench, to form a native oxide film.

[0060] The conditions for forming the native oxide film are exemplified as follows: Natural oxide film formation atmosphere: Air with humidity of 50% or more Natural oxide film formation temperature: room temperature (25℃) or higher Natural oxide film formation time: 1000 minutes or more

[0061] Even by leaving the laminated wafer 20 in the air under the above-mentioned conditions, the exposed region of the support surface 12s can be oxidized to form a natural oxide film as the insulating film 14 on the exposed region of the support surface 12s, thereby inactivating the exposed region of the support surface 12s. However, the above-mentioned annealing or ultraviolet light irradiation is preferable from the viewpoint of being able to reliably cover the entire exposed region of the support surface 12s with the insulating film 14, etc.

[0062] (molding process) After step C is completed, the laminated wafers 20 are shaped to obtain electrodes 10 having a predetermined shape (for example, chip shape).

[0063] Specifically, as shown in FIG. 4(b), a concave groove 21 (e.g., a scribed groove) is formed on the back surface (the surface opposite to the support surface 12s) of the laminated wafer 20. The concave groove 21 can be formed by using a known method such as a laser processing method such as laser scribing or laser dicing, a mechanical processing method, or etching. It is preferable that the concave groove 21 is formed so as not to penetrate the support 12 in the thickness direction, that is, so as not to reach the diamond portion 11. It is preferable that the concave groove 21 is formed so that the thickness of the thinnest part of the support 12 is, for example, 10 μm or more and 80 μm or less. By providing the concave groove 21 in this way, it is possible to suppress the deterioration of the diamond portion 11 and to further prevent the deterioration of the sensitivity of the electrode 10. The deterioration of the diamond portion 11 can be, for example, the sp of the granular crystals 11a. 3 Bond is sp 2 This means that the material changes into bonds, i.e., becomes graphitized.

[0064] 4(c), the support 12 is broken along the concave groove 21. At this time, it is preferable to break the support 12 by bending the diamond portion 11 outward along the concave groove 21.

[0065] As described above, the diamond portion 11 is composed of a plurality of granular crystals 11a, and gaps exist between the granular crystals 11a. Therefore, since the diamond portion 11 is separated by the gaps between the granular crystals 11a, the chip-shaped electrode 10 having the diamond portion 11 and the support 12 can be obtained by simply breaking the support 12. In this way, because there are gaps between the granular crystals 11a, even if the diamond portion 11 has a high hardness, the chip-shaped electrode 10 can be obtained accurately, stably, and easily by the above-mentioned method using breaking.

[0066] The diamond portion 11 of the electrode 10 obtained by the above-mentioned technique using fracture is less likely to have a fracture surface on its side. That is, the diamond portion 11 has almost no fracture surface, and preferably, the diamond portion 11 has no fracture surface. In addition, since the diamond portion 11 is not fractured by the above-mentioned technique using fracture, the diamond portion 11 is less likely to overhang from the support surface 12s. Therefore, the projection image of the diamond portion 11 (granular crystals 11a) onto the support surface 12s is entirely contained within the support surface 12s. That is, the diamond portion 11 does not have a region that overhangs from the support surface 12s.

[0067] It is also possible to form the concave grooves 21 from the front surface side (the diamond portion 11 side) of the laminated wafer 20. However, since the diamond portion 11 has a high hardness, it is difficult to form the concave grooves 21 from the diamond portion 11 side by laser processing, mechanical processing, or the like.

[0068] It is also possible to obtain the electrode 10 by forming the laminated wafers 20 into a predetermined shape by dry etching or the like. However, it is very difficult to form the laminated wafers 20 having the high-hardness diamond portions 11 into a predetermined shape by dry etching or the like. Furthermore, dry etching may cause altered areas in the diamond portions 11.

[0069] (5) Effects According to this aspect, one or more of the following advantages can be obtained.

[0070] (a) By forming the diamond portion 11 from a plurality of granular crystals 11a, the diamond portion 11 has gaps between the granular crystals 11a.

[0071] This makes it possible to improve the ease of processing, processing yield, and processing accuracy of the electrode 10. For example, even if the electrode has a high-hardness diamond portion 11, it is possible to easily obtain a chip-shaped electrode 10 with high accuracy, stability, and accuracy by the above-mentioned technique using fracture. It is also possible to reduce the size (planar area) of the electrode 10. As a result, it is possible to improve the productivity of the electrode 10 and reduce the manufacturing cost.

[0072] Furthermore, even if there is a difference between the thermal expansion coefficient of diamond and the thermal expansion coefficient of the support 12, the stress caused by the difference between these thermal expansion coefficients can be alleviated, and the diamond portion 11 can be prevented from peeling off from the support surface 12s. As a result, it is possible to prevent a decrease in the diamond portion 11 that contributes to sensing, and to prevent a decrease in the sensitivity of the electrode 10. As a result, it is possible to improve the reliability of the electrode 10 and the reliability of a sensor having the electrode 10.

[0073] On the other hand, if the diamond portion 11 is made of a diamond film, it is difficult to form the electrode 10, and the processing yield and processing accuracy are reduced. In this case, the stress caused by the above-mentioned difference in thermal expansion coefficient cannot be alleviated, and the diamond film, which is hard and resistant to warping, is likely to peel off from the support surface 12s.

[0074] (b) By alleviating the stress caused by the difference in thermal expansion coefficient, the laminate (laminate wafer 20) of diamond portion 11 and support 12 before being formed into electrode 10 is less likely to warp. It is also possible to reduce the residual stress in diamond portion 11. As a result, the processing precision, processing yield, and productivity of electrode 10 can be further improved.

[0075] (c) By providing the diamond portion 11 so that a portion of the support surface 12s is exposed, the growth of the diamond portion 11 can be completed in a shorter time than in the case where the entire support surface 12s is covered with the diamond portion 11 (for example, in the case where a diamond film is formed). This reduces the cost of raw materials for forming the diamond portion 11, and therefore the manufacturing cost of the electrode 10. Furthermore, less material adheres to the inside of the growth chamber 301 of the thermal filament CVD apparatus 300, and the number of times the growth chamber 301 needs to be cleaned can be reduced, thereby further improving productivity and further reducing manufacturing costs.

[0076] (d) The coverage of the support surface 12s by the diamond portion 11 is 15% or more and 90% or less, so that the electrode 10 can be suitably used as a working electrode of an electrochemical sensor, while the diamond portion 11 having gaps can be reliably obtained. This makes it possible to improve the ease of processing, processing yield, and processing accuracy of the electrode 10, and also to reliably obtain the above-mentioned stress relaxation effect, thereby making it possible to increase the reliability of the electrode 10. In addition, the surface area of ​​the diamond portion 11 can be made larger than the plane area of ​​the support surface 12s, or larger than when the diamond portion 11 is made of a diamond film, etc., and therefore the sensitivity of the electrode 10 can be increased.

[0077] If the coverage exceeds 90%, it becomes difficult to obtain the diamond portion 11 having gaps. This makes it difficult to form the electrode 10, and the processing yield and processing accuracy of the electrode 10 may decrease. In addition, it becomes difficult to obtain the above-mentioned stress relaxation effect, and peeling off of the granular crystals 11a cannot be avoided, which may decrease the sensitivity and reliability of the electrode 10. If the coverage is less than 15%, the surface area of ​​the diamond portion 11 is too small, and the electrode 10 may not be usable as a working electrode of a sensor for electrochemical measurement.

[0078] (e) By setting the average grain size of the granular crystals 11a to 60 nm or more and 150 nm or less, adverse effects caused by grain boundaries between the granular crystals 11a can be prevented from becoming apparent, and it is possible to further improve the reliability of the electrode 10 and the accuracy of electrochemical measurements. In addition, it is also possible to easily obtain an electrode 10 having the above-mentioned coverage rate of 15% or more and 90% or less.

[0079] On the other hand, if the average grain size is more than 150 nm, the diamond portion 11 may not have any gaps, or even if it does have gaps, the gaps may be small. This may reduce the ease of processing, processing yield, and processing accuracy of the electrode 10, and may not fully achieve the above-mentioned stress relaxation effect. If the average grain size is less than 60 nm, the number of crystal grain boundaries present in the diamond portion 11 increases, and it is not possible to avoid the adverse effects of the grain boundaries from becoming apparent, which may reduce the reliability of the electrode 10 or the accuracy of the electrochemical measurement.

[0080] (f) Since the multiple granular crystals 11a are randomly present on the support surface 12s, it is possible to prevent variations in sensitivity within one electrode 10. This makes it possible to perform accurate electrochemical measurements, for example, even if only a small amount of test liquid is supplied to a sensor having the electrode 10 during electrochemical measurement.

[0081] (g) The region of the support surface 12s that is not in contact with the granular crystals 11a, i.e., the exposed region of the support surface 12s, is inactivated, so that the oxidation-reduction reaction of uric acid can be prevented from occurring on the exposed region of the support surface 12s during electrochemical measurement, thereby making it possible to further improve the accuracy of the electrochemical measurement.

[0082] (h) By carrying out the above-mentioned step C to inactivate the exposed area of ​​the support surface 12s, it is possible to reliably cover the entire exposed area of ​​the support surface 12s with the insulating film 14. This reliably prevents the oxidation-reduction reaction of uric acid from occurring on the exposed area of ​​the support surface 12s, and makes it possible to further improve the accuracy of the electrochemical measurement.

[0083] Even if the above-mentioned step C is not performed intentionally, a natural oxide film is usually formed on the exposed area of ​​the support surface 12s. However, this natural oxide film often cannot completely cover the entire exposed area of ​​the support surface 12s, and passivation is often insufficient. In contrast, in this embodiment, a process for passivating the exposed area of ​​the support surface 12s (i.e., step C) is performed. This allows the exposed area of ​​the support surface 12s to be sufficiently passivated, and the entire exposed area of ​​the support surface 12s can be completely covered with the insulating film 14.

[0084] <Other aspects> Although the embodiments of the present disclosure have been specifically described above, the present disclosure is not limited to the above embodiments and can be modified in various ways without departing from the spirit and scope of the present disclosure.

[0085] For example, a functional membrane that allows a specific component (for example, only uric acid) to permeate or reacts only with this specific component may be provided on the diamond portion 11. As such a functional membrane, for example, a membrane containing a specific enzyme corresponding to the detection component or a specific surface decoration membrane such as an ion exchange membrane may be provided.

[0086] Also, for example, in step C, if the exposed region of the support surface 12s can be inactivated, the inactivation treatment may be performed using a method other than the above-mentioned annealing, ultraviolet light irradiation, and leaving in clean air. For example, instead of the above-mentioned annealing, ultraviolet light irradiation, or leaving in clean air, the inactivation treatment may be performed using various acids, hydrogen peroxide solution, water, etc. As such a method, a method of inactivating the exposed region of the support surface 12s by immersing in pure water containing oxygen or a solution containing an oxidizing agent and performing chemical etching may be considered. Also, in step C, the inactivation treatment may be performed by appropriately combining a plurality of methods among the above-mentioned annealing, ultraviolet light irradiation, leaving in clean air, chemical etching, etc.

[0087] In the above embodiment, step C is performed before the molding process, but this is not limiting. For example, step C may be performed after the molding process.

[0088] In the above embodiment, the sample liquid is urine, but is not limited thereto. The sample liquid may be urine, blood, tears, snot, saliva, sweat, or other bodily fluids. The sample liquid is not limited to human origin, but may be animal origin. In the above embodiment, the sample liquid is electrolyzed as a specific component contained in the sample liquid, but is not limited thereto. If the voltage applied to the sensor having the electrode 10 is within a predetermined voltage range, the voltage sweep conditions of cyclic voltammetry can be appropriately changed to measure the concentrations of various components (substances).

[0089] In the above embodiment, the electrode 10 is used as a working electrode of an electrochemical sensor, but is not limited thereto. For example, the electrode 10 can be used as an electrolysis electrode (e.g., an electrolysis electrode for an ozone generator) for use in electrolysis or synthesis of compounds, electrolysis of water, etc. EXAMPLES

[0090] Hereinafter, experimental results that support the effects of the above-mentioned embodiment will be described.

[0091] A 6-inch circular Si substrate in plan view was prepared as a support, and a predetermined scratching process was performed on the main surface of the Si substrate, which was to be the support surface of the diamond portion (i.e., the crystal growth surface). Then, using the hot filament CVD apparatus shown in FIG. 3 and a tungsten filament as the filament, diamond crystals were grown on the scratched support surface to provide the diamond portion, and laminated wafers (samples 1 to 8) were fabricated as laminates of the Si substrate and the diamond portion. When fabricating each sample, the crystal growth time was adjusted to vary the coverage of the support surface by the diamond portion. The other growth conditions, except for the growth time, were set to the same predetermined conditions within the range of conditions described in the above-mentioned embodiment. Thereafter, the laminated wafers (samples 2 to 8) whose coverage was not 100% were annealed in an O-containing atmosphere to perform a predetermined inactivation process. The annealing conditions were set to the same predetermined conditions within the range of conditions described in the above-mentioned embodiment.

[0092] Then, a galvano optical laser was used to irradiate the back surface (the surface opposite to the surface on which the diamond portion was provided) of the Si substrate of Samples 1 to 8 with laser light (532 nm, 5 W, 10 kHz, spot diameter 2 μm) in a lattice pattern with a pitch of 2 mm at a scanning speed of 10 cm / sec, forming lattice-shaped laser grooves (concave grooves). The number of scans of the laser light was four. After that, breaking (fracturing) was performed along the laser grooves under the conditions of a break push-in amount of 0.1 mm and a break speed of 100 mm / s, and multiple chip-shaped electrodes with a size of 2 mm square were produced from each of Samples 1 to 8.

[0093] (evaluation) SEM images were taken of the electrodes made from Samples 1 to 8. The taken SEM images are shown in Figures 5 to 12, respectively. The "planar SEM images" in Figures 5 to 12 are SEM images taken from the diamond portion side of the electrode, i.e., SEM images of the electrode in the planar direction of the support surface, and the "cross-sectional SEM images" are SEM images of the longitudinal section of the electrode, i.e., SEM images of the electrode in the direction perpendicular to the support surface.

[0094] The coverage and average grain size of Samples 1 to 8 were measured. The coverage of Samples 1 to 8 was calculated by binarizing the planar SEM images obtained and calculating the ratio of the area of ​​the diamond portion (for example, the white portion) to the total area of ​​the binarized image. The average grain size of Samples 1 to 8 was calculated by image analysis of the planar SEM images obtained using the method described in the above embodiment. In Sample 1, the coverage was 100% and the average grain size was 220 nm. In Sample 2, the coverage was 98% and the average grain size was 165 nm. In Sample 3, the coverage was 84% ​​and the average grain size was 121 nm. In Sample 4, the coverage was 72% and the average grain size was 115 nm. In Sample 5, the coverage was 66% and the average grain size was 96 nm. In Sample 6, the coverage was 31% and the average grain size was 79 nm. In Sample 7, the coverage was 15% and the average grain size was 62 nm. In Sample 8, the coverage was 1.2% and the average grain size was 45 nm.

[0095] In addition, an electrochemical sensor as shown in FIG. 13 was fabricated using the electrodes fabricated from Samples 1 to 8 as working electrodes. Then, using this electrochemical sensor, the uric acid concentration in the test solution was measured by cyclic voltammetry to obtain a cyclic voltammogram. The cyclic voltammetry was performed under the same predetermined conditions within a voltage range including -1100 mV to 1500 mV and a sweep rate range of 0.1 V / s to 1 V / s. The obtained cyclic voltammograms (CV) are shown in FIG. 5 to FIG. 12, respectively.

[0096] From the cross-sectional SEM image of FIG. 5 in particular, it can be seen that when the coverage is 100%, the diamond portion is a continuous film made of diamond, and the diamond portion cannot be composed of granular crystals.

[0097] Also, from FIG. 6, it can be seen that when the coverage is 98%, although the diamond portion can be composed of granular crystals, the diamond portion has almost no gaps or spaces between the granular crystals.

[0098] From Figures 7 and 11, it can be seen that when the coverage is 84% ​​or 15%, the diamond part is composed of granular crystals, but there are certain gaps and spaces between the granular crystals. It can also be seen that when the coverage is 84% ​​or 15%, the oxidation current peak in the cyclic voltammogram is higher than when the coverage is 100%. From this, it can be seen that when the coverage is 15% or more and 90% or less, the sensitivity of the electrode is higher than when the coverage is over 90%. In other words, it can be seen that the accuracy of the electrochemical measurement can be improved compared to when the coverage is over 90%.

[0099] From Figures 8 and 10, it can be seen that when the coverage is 72% or 31%, the diamond part is composed of granular crystals, but there are sufficient gaps and spaces between the granular crystals. It can also be seen that when the coverage is 72% or 31%, the oxidation current peak in the cyclic voltammogram is higher and sharper than when the coverage is 84% ​​or 15%. From this, it can be seen that when the coverage is 30% or more and 75% or less, the sensitivity of the electrode can be increased, and the accuracy of the electrochemical measurement can be improved.

[0100] From FIG. 9, it can be seen that when the coverage is 66%, the diamond part is composed of granular crystals, but there are sufficient gaps and spaces between the granular crystals. It can also be seen that when the coverage is 66%, the oxidation current peak in the cyclic voltammogram is higher and sharper than when the coverage is 72% or 31%. From this, it can be seen that when the coverage is around 65% (for example, 60% or more and 70% or less), the sensitivity of the electrode can be further increased, and the accuracy of the electrochemical measurement can be further improved. Note that in FIG. 9, the vertical axis scale of the CV graph is different from that of the CV graphs shown in FIGS. 6 to 8, 10, and 11.

[0101] 12, it can be seen that when the coverage is less than 15% (e.g., 1.2%), an oxidation current peak cannot be observed in the cyclic voltammogram, and the electrode cannot be used as a working electrode of an electrochemical sensor. In other words, when the coverage is 15% or more, an oxidation current peak can be observed in the cyclic voltammogram, and the electrode can be suitably used as a working electrode of an electrochemical sensor.

[0102] In addition, the processing yield of the electrodes obtained from samples 1 to 8 was evaluated. Specifically, first, the electrodes obtained from samples 1 to 8 were inspected using an automatic appearance inspection device, and electrodes whose planar area was within ±2% of the reference value and whose angles of each side were within 90°±2° were deemed to be acceptable. Then, the processing yield was calculated from the following (Equation 1). The processing yields (%) of samples 1 to 8 are shown in Table 1 below. (Number 1) Processing yield (%) = (number of acceptable electrodes / total number of electrodes obtained from each sample) x 100

[0103] [Table 1]

[0104] From Table 1, we can see that the electrode processing yield can be improved by having the diamond part composed of granular crystals. In addition, the lower the coverage, the higher the processing yield, and the processing yield is 90% or more when the coverage is 75% or less.

[0105] <Preferred aspects of the present disclosure> Preferred aspects of the present disclosure will be described below.

[0106] (Appendix 1) According to one aspect of the present disclosure, A support formed of a material other than diamond; a diamond portion supported on a support surface which is at least one of the surfaces of the support; The diamond portion is composed of a plurality of granular diamond crystals, An electrode is provided, with a portion of the support surface exposed.

[0107] (Appendix 2) The electrode according to claim 1, preferably 2. The electrode according to claim 1, wherein the ratio of the projected area of ​​the plurality of granular diamond crystals onto the support surface to the planar area of ​​the support surface is 15% or more and 90% or less, preferably 30% or more and 75% or less.

[0108] (Appendix 3) The electrode according to claim 1 or 2, preferably The surface area of ​​the diamond portion is greater than the planar area of ​​the support surface of the support body.

[0109] (Appendix 4) The electrode according to any one of Supplementary Notes 1 to 3, preferably The average grain size of the plurality of granular diamond crystals is 60 nm or more and 150 nm or less, preferably 75 nm or more and 125 nm or less.

[0110] (Appendix 5) The electrode according to any one of Supplementary Notes 1 to 4, preferably The plurality of granular diamond crystals are randomly disposed on the support surface.

[0111] (Appendix 6) The electrode according to any one of Supplementary Notes 1 to 5, preferably An insulating film is formed on the support surface in the region (exposed region) where the plurality of granular diamond crystals are not in contact. That is, the inactivation of the support surface in the region where the plurality of granular diamond crystals are not in contact is achieved by forming an insulating film on the support surface in the region where the plurality of granular diamond crystals are not in contact.

[0112] (Appendix 7) The sensor according to claim 6, preferably comprising: The insulating film has a thickness of 1 nm or more, The insulating film entirely covers the support surface in an area not in contact with the plurality of granular diamond crystals.

[0113] (Appendix 8) The electrode according to any one of Supplementary Notes 1 to 7, preferably The support is formed using silicon or a silicon compound, and is preferably made of any one of a single crystal silicon substrate, a polycrystalline silicon substrate, and a silicon carbide substrate.

[0114] (Appendix 9) The electrode according to any one of Supplementary Notes 1 to 8, preferably The diamond portion is doped with boron at 1×10 19 cm -3More than 1×10 22 cm -3 Contains the following concentrations:

[0115] (Appendix 10) The electrode according to any one of Supplementary Notes 1 to 9, preferably The electrode is used as a working electrode in electrochemical measurements and is preferably a chip-shaped electrode having a rectangular outer shape in a plan view.

[0116] (Appendix 11) The electrode according to any one of Supplementary Notes 1 to 10, preferably The diamond portion does not have a fracture surface.

[0117] (Appendix 12) The electrode according to any one of Supplementary Notes 1 to 11, preferably The diamond portion has no residual stress.

[0118] (Appendix 13) The electrode according to any one of Supplementary Notes 1 to 12, preferably The projection image of the diamond portion onto the support surface is entirely contained within the support surface, i.e., the diamond portion does not have an area that overhangs the support surface.

[0119] (Appendix 14) According to another aspect of the present disclosure, A method for manufacturing an electrode is provided, which includes a step of providing a diamond portion on a support surface, which is at least one surface of a support formed of a material other than diamond, by growing a plurality of granular diamond crystals on the support surface so that a portion of the support surface is exposed.

[0120] (Appendix 15) The method according to claim 14, preferably comprising: In the step of providing the diamond portion, the plurality of granular diamond crystals are grown so that the ratio of the projected area of ​​the plurality of granular diamond crystals on the support surface to the planar area of ​​the support surface is 15% to 90%, preferably 30% to 75%. Preferably, in the step of providing the diamond portion, the plurality of granular diamond crystals are grown so that the average grain size is 60 nm to 150 nm, preferably 75 nm to 125 nm.

[0121] (Appendix 16) The method according to claim 14 or 15, preferably comprising a step of performing a predetermined seeding treatment or scratching treatment on the support surface of the support before the step of providing the diamond portion; The step of providing the diamond portion comprises growing the plurality of granular diamond crystals randomly on the support surface.

[0122] (Appendix 17) The method according to any one of appendices 14 to 16, preferably comprising: The method further includes passivating areas of the support surface not contacted by the plurality of granular diamond crystals.

[0123] (Appendix 18) The method according to claim 17, preferably comprising: In the inertization step, an annealing treatment is performed on the laminate having the support and the diamond portion in an oxygen-containing atmosphere or a nitrogen-containing atmosphere. [Explanation of symbols]

[0124] 10 electrodes 11 Diamond Club 11a Granular diamond crystals 12 Support 12s support surface

Claims

1. A support body formed by processing a substrate made of a material other than diamond into a chip shape; a diamond portion supported on a support surface which is one of the main surfaces of the support, The diamond portion is composed of a plurality of granular diamond crystals, all of said plurality of granular diamond crystals are in direct contact with said support surface; A tip-like electrode, wherein the ratio of the projected area of ​​the plurality of granular diamond crystals onto the support surface to the planar area of ​​the support surface is 15% or more and 90% or less.

2. 2. The electrode of claim 1, wherein the average grain size of the plurality of granular diamond crystals is between 60 nm and 150 nm.

3. 3. The electrode of claim 1 or 2, wherein the plurality of granular diamond crystals are randomly present on the support surface.

4. An electrode as described in any one of claims 1 to 3, wherein an insulating film formed by inactivating the support is formed in an area of ​​the support surface where the plurality of granular diamond crystals are not in contact.

5. 5. The electrode according to claim 1, wherein the support is formed using a silicon element or a silicon compound.

6. The diamond portion is doped with boron at 1×10 19 cm -3 Above 1 x 10 22 cm -3 The electrode according to any one of claims 1 to 5, comprising the following concentrations:

7. The electrode according to any one of claims 1 to 6, which is used as a working electrode in electrochemical measurements.

8. A method for manufacturing an electrode, comprising a step of growing a diamond portion composed of a plurality of granular diamond crystals on a support surface, which is at least one of the surfaces of a support body formed of a material other than diamond, wherein the ratio of the projected area of ​​the plurality of granular diamond crystals onto the support surface to the planar area of ​​the support surface is 15% or more and 90% or less.

9. 9. The method of claim 8, further comprising the step of passivating areas of the support surface not contacted by the plurality of granular diamond crystals.

10. 10. The method for manufacturing an electrode according to claim 9, wherein in the passivation step, an annealing treatment is performed on the laminate having the support and the diamond portion in an oxygen-containing atmosphere or a nitrogen-containing atmosphere.

Citation Information

Patent Citations

  • Method for manufacturing diamond electrode

    JP2007238989A

  • Diamond electrode and sensor equipped with the same

    JP2007292717A

  • Conductive diamond film-formed substrate, and method for production of the substrate

    JP2009091234A

  • Conductive diamond electrode and method for manufacturing the same

    JP2013076130A

  • Measuring device for reduced glutathione using diamond microelectrode

    JP2013208259A